Focal segmental glomerulosclerosis in children complicated by posterior reversible encephalopathy syndrome. Issue 3 (March 2018) - Stârcea, Magdalena; Gavrilovici, Cristina; Munteanu, Mihaela; Miron, Ingrith
An uncommon side effect of cyclosporine A (CsA) use is posterior reversible encephalopathy syndrome (PRES). PRES usually develops because of disturbed capacity of posterior cerebral blood flow to autoregulate an acute rise in blood pressure. We present the case of a 10-year-old girl who was previously diagnosed in our department with focal segmental glomerulosclerosis. She was treated with CsA and developed seizures, progressive loss of consciousness, and visual disturbance on the 7th day of treatment. Brain magnetic resonance imaging showed degeneration of white matter with diffuse demyelination in the parietal and posterior occipital lobes, consistent with the diagnosis of PRES. Cases of PRES reported in children are usually secondary to immunosuppressive therapy in oncological and haematological diseases. Our case is the fifth reported case of focal segmental glomerulosclerosis in children treated with CsA and complicated by PRES. Rapid recognition of PRES and stopping neurotoxic therapy early are essential for a good prognosis.